A case report of osteoblastoma on the distal phalanx of the ring finger successfully treated with curettage and polymethylmethacrylate filling. (2015) - Gumustas, Seyit Ali; Cagırmaz, Talat; Guler, Olcay; Ofluoglu, Onder; Kayahan, Sibel
Highlights: This is the first report of osteoblastoma on the distal phalanx. The finger was monitored closely for two years; sequential films showed a radiopaque interface and no evidence of local recurrence. Abstract: Background: Osteoblastoma is an aggressive benign tumor whose presentation varies with location and size. This rare bone tumor is thus difficult to diagnose particularly when it occurs outside its most common location – the vertebral column and long bones. Case: We report a case of osteoblastoma of the fourth distal phalanx of the left hand in an 18-year-old male, presented with pain and swelling and treated with curettage and polymethylmethacrylate filling followed by immobilization by a cast, which was opened 10 days later to start physical therapy. Patient was pain-free, recovered full function of his finger, and remained without pain at one month post-surgery. The finger was monitored closely for two years; sequential films showed a radiopaque interface and no evidence of local recurrence. Conclusion: This is the first report of osteoblastoma on the distal phalanx. The possibility of osteoblastoma should be considered in cases of pain and swelling of phalanx, and if diagnosed, curettage and polymethylmethacrylate filling may be the treatment of choice.